Understanding the composition-dependent stability of η phase for future Ni-Co-based superalloys. (October 2022) - Yu, Xin; Yu, Zichao; Zhang, Lina; Yu, Hongyao; Zhao, Lei; Zhang, Wenyan; Ruan, Jingjing; Wang, Zi; Cui, Huijie; Bi, Zhongnan; Jiang, Liang; Zhu, Lilong
Abstract: Knowledge associated with the alloying effects of Al, Ti, Ta and Nb on phase stability of Ni-Co-based superalloys plays a significant role in efficiently exploring the multi-component space for future alloy designs, and thus were systematically investigated using a high-throughput dual-anneal multi-component diffusion multiple (MCDM) approach. In this work, η phase presenting considerably different morphology and spatial distribution was confirmed in the Ta-rich and Nb-rich alloys, and its zero-phase-fraction (ZPF) line at 800 °C was determined that suggests a maximum Nb + Ta content of about 2.5 at.% while avoiding the η formation. The composition criterion regarding the stability of η was updated by taking into account the destabilizing effect of Co such that the η formation can be significantly suppressed with increasing Co from a critical level of about 12 at.%, providing essential guidance to design alloy chemistry for superior microstructural stability at high-temperature service conditions. Graphical abstract: Image, graphical abstract